Research of MFG-E8, OPG and SOCS-3 on preeclampsia - Ilhan, Fulya; Atabay, Hatice; Ozkan, Zehra Sema; Doni, Nebiye Yentur; Can, Sevim Tuncer (Amer Assoc Immunologists, 2016)
[Abstract Not Available]
Annual Meeting of the American-Association-of-Immunologists (AAI) -- MAY 13-17, 2016 -- Seattle, WA